Variability and reliability of gait kinematic parameters after controlled tripping in older adults: a preliminary study (Journal of Physical Education (Maringá), 2017)
Approximately 21% of the falls in older adults occur due to tripping, while walking. There is a paucity of information regarding the gait variability and reliability when a tripping is induced in different days mainly with elderly. It was aimed to analyze the variability and the reliability (intra- and inter-day) of spatiotemporal gait parameters and joint angles after controlled tripping in older adults. Eight healthy older women participated. The trip was induced during the early-mid swing phase on the transposing segment and the kinematic data was obtained from trials. The variability and reliability of spatiotemporal gait parameters and joint angles during the gait cycle were checked through the coefficient of variation (CV), the intraclass coefficient correlation (ICC) and the standard error of measurement (SEM). The variability of spatiotemporal and intra- and inter-day angular parameters was low for most variables, except for plantar flexion. The SEM was low for all parameters. Intra-day reliability was moderate to high for the spatiotemporal and angular parameters. Inter-day reliability was considered low to moderate for all parameters. The variables did not differ between instants and days. Experimental procedures demonstrate that the walking pattern did not change, but should be considered with caution in studies that include intervention, particularly for angular parameters during gait.